Da vesle Agnar ble ekstrem - Nilsen, Yngve (Tidsskrift for kulturforskning, 2014)
Since the turn of the millennia, the term "extreme weather" has been used very frequently in Norwegian media. It first appeared in the mid-1990s. This article tries to explain the rise of this new category of weather, by a historical comparison between the establishment of a Norwegian storm warning system in the second half of the 19th century and the establishment of a Norwegian extreme weather warning system by the end of the 20th. In both cases, the state was active. In the first case by establishing a national Meteorological institute and covering the necessary telegraph expenses for warnings by telegraph. In the second case by making this Meteorological institute a part of a new national system for protection against disasters. Both events were stages in a long term process of giving bad weather individuality, in order to make the warnings recognizable in growing currents of electronic information. However, extreme weather is not defined by physical properties, but by its expected economic, technical and social consequences. Thus, it's not a meteorological term, but an institutional one.